Theatre in a new democracy : some major trends in South African theatre from 1994 to 2003 - Van Heerden, Johann (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DPhil (Dept. of Drama.Centre for Theatre Research))--University of Stellenbosch, 2008.